2002
DOI: 10.1300/j013v36n04_09
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory Variance in Bulimia Nervosa

Abstract: In order to prevent disease, one must understand the factors that contribute to the variance of the illness. In an effort to better understand factors that contribute to bulimia nervosa (BN), a study was designed to investigate explanatory factors in BN. Of particular interest to the researchers in the study was the effect of the Hispanic subculture on the variance of BN. Female participants (n = 372) and male participants (n = 109) from the ages of 17-49 agreed to serve in the study. A self-report scale desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
(12 reference statements)
0
10
1
Order By: Relevance
“…Latin culture favours a curvy, full-bodied figure that is at odds with the western thin ideal female body type; hence, Hispanic women may be adversely affected by Western culture’s beauty and thinness ideals (Gil-Kashiwabura, 2002; Viladrich, Yeh, Bruning, & Weiss, 2009). Compared to white women, Hispanic women report equal to and higher levels of appearance concerns, body dissatisfaction, body shame and eating disorder symptomatology (Boisvert & Harrell, 2009a; Breitkopf, Littleton, & Berenson, 2007; Croll, Neumark-Sztainer, Story, & Ireland, 2002; McComb & Clopton, 2002; Robinson et al, 1996). Hispanic women report a greater desire to lose weight and drive for thinness, and a greater prevalence of weight-related behaviours such as binge eating, vomiting and use of diet pills, laxatives or diuretics, than white women (Bisaga et al, 2005; Croll et al, 2002; Fitzgibbon et al, 1998; Smith & Krejci, 1991; Snow & Harris, 1989; Story, French, Resnick, & Blum, 1995).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Latin culture favours a curvy, full-bodied figure that is at odds with the western thin ideal female body type; hence, Hispanic women may be adversely affected by Western culture’s beauty and thinness ideals (Gil-Kashiwabura, 2002; Viladrich, Yeh, Bruning, & Weiss, 2009). Compared to white women, Hispanic women report equal to and higher levels of appearance concerns, body dissatisfaction, body shame and eating disorder symptomatology (Boisvert & Harrell, 2009a; Breitkopf, Littleton, & Berenson, 2007; Croll, Neumark-Sztainer, Story, & Ireland, 2002; McComb & Clopton, 2002; Robinson et al, 1996). Hispanic women report a greater desire to lose weight and drive for thinness, and a greater prevalence of weight-related behaviours such as binge eating, vomiting and use of diet pills, laxatives or diuretics, than white women (Bisaga et al, 2005; Croll et al, 2002; Fitzgibbon et al, 1998; Smith & Krejci, 1991; Snow & Harris, 1989; Story, French, Resnick, & Blum, 1995).…”
Section: Introductionmentioning
confidence: 93%
“…Hispanic women report a greater desire to lose weight and drive for thinness, and a greater prevalence of weight-related behaviours such as binge eating, vomiting and use of diet pills, laxatives or diuretics, than white women (Bisaga et al, 2005; Croll et al, 2002; Fitzgibbon et al, 1998; Smith & Krejci, 1991; Snow & Harris, 1989; Story, French, Resnick, & Blum, 1995). Hispanic women tend to have higher BMI than white women, with overweight and obesity identified as a risk factor for weight control behaviours in Hispanic women and girls (Breitkopf et al, 2007; Fitzgibbon et al, 1998; McComb & Clopton, 2002; Robinson et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…There are three primary subscales (DT 3 B 4 , and BD 5 ) on the EDI-3 that create the EDRC 6 . Researchers have used the DT (Cashel, Cunningham, Landeros, Cokley, & Muhammad, 2003; Franko & George, 2008; Gordon, Castro, Sitnikov, & Holm-Denoma, 2010; McComb & Clopton, 2002; Pidcock, Fischer, & Munsch, 2001), B (Cashel et al, 2003; Gordon et al, 2010; Perez, Voelz, Pettit, & Joiner, 2002), and/or BD (Cashel et al, 2003; Franko & George, 2008; Gordon et al, 2010; McComb & Clopton, 2002; Perez et al, 2002) subscales from earlier versions of the EDI with samples that included LCW and the subscales of the EDRC demonstrated good reliability (Gordon et al, 2010; Pidcock et al, 2001). However, the factor structure of any assessment of eating pathology should be tested to determine if it appropriately conceptualizes these concerns in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Boisvert and Harrell (2009) found that Hispanic women living in Alberta, Canada, experienced higher body dissatisfaction than White women ( M = 3.40, SD = 1.40, vs. M = 2.68, SD = 1.01), and engaged in more bulimic behavior, for example, binge eating, than White women ( M = 3.25, SD = 1.23, vs. M = 2.24, SD = 1.00). Studies conducted in the United States using these measures found no significant differences in the body dissatisfaction, drive for thinness, and eating disorder symptomatology scores between Hispanic and White women (Gordon, Castro, Sitnikov, & Holm-Denoma, 2010; McComb & Clopton, 2002). This discrepancy in results might be attributed to the smaller Hispanic population in Alberta than that of the United States.…”
Section: Body Dissatisfactionmentioning
confidence: 90%
“…Bulimic symptomatology is measured using the Bulimia Test-Revised subscale of the EDI (BULIT 2 ), which questions participants on binge eating and purging behaviors and assesses risk for bulimia nervosa. A sample item on this questionnaire is, “I stuff myself with food” (Boisvert & Harrell, 2009; McComb & Clopton, 2002). Participants respond to questions on a 6-point Likert-type scale ranging from 1 ( never ) to 6 ( always ), where a higher score indicates increased bodily dissatisfaction.…”
Section: Body Dissatisfactionmentioning
confidence: 99%